Trichoderma brevicompactum 6311: Prevention and Control of Phytophthora capsici and Its Growth-Promoting Effect - Jien Zhou; Junfeng Liang; Xueyan Zhang; Feng Wang; Zheng Qu; Tongguo Gao; Yanpo Yao; Yanli Luo (Journal of Fungi)
Pepper Phytophthora blight caused by Phytophthora capsici results in substantial losses in global pepper cultivation. The use of biocontrol agents with the dual functions of disease suppression and crop growth promotion is a green and sustainable way of managing this pathogen. In this study, six biocontrol strains of Trichoderma with high antagonistic activity against P. capsici were isolated and screened from the rhizosphere soil of healthy peppers undergoing long-term continuous cultivation. Morphological identification and molecular biological identification revealed that strains 2213 and 2221 were T. harzianum, strains 5111, 6311, and 6321 were T. brevicompactum, and strain 7111 was T. virens. The results showed that T. brevicompactum 6311 had the greatest inhibitory effect against P. capsici. The inhibition rate of 6311 on the mycelial growth of P. capsici was 82.22% in a double-culture test, whereas it reached 100% in a fermentation liquid culture test. Meanwhile, the pepper fruit tests showed that 6311 was 29% effective against P. capsici on pepper, and a potting test demonstrated that the preventive and controlling effect of 6311 on pepper epidemics triggered by P. capsici was 55.56%. The growth-promoting effect, germination potential, germination rate, radicle-embryonic axis length, germination index, and fresh weight of peppers cultured in the 6311 fermentation broth were significantly increased compared with the results for the control group. Scanning electron microscopy revealed that 6311 achieved the parasitism of P. capsici, producing siderophores and the growth hormone indoleacetic acid (IAA) to achieve disease-suppressive and growth-promoting functions. Transcriptomic results indicated that genes encoding proteins involved in plant disease resistance, namely flavanone 3-hydroxylase (F3H) and growth transcription factor (AUX22), were generally upregulated after the application of 6311. This study demonstrated that 6311 exhibits significant bioprotective and growth-promoting functions.